(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
This article describes the linguistic markers that characterize the state of conflicting and unconflicting of individuals during the process of interpersonal communication, its speech and protective mechanisms in the conflict interaction.